JEJARING SOSIAL/FACEBOOK SEBAGAI MEDIA E-PENGECER ( Studi kasus mahasiswa di Kota Denpasar) - Ekawati, Ni Wayan (Buletin Studi Ekonomi; Vol 17.No.2.Agustus 2012 (PP.99-225), 2012)
Abstract: Social Network/ Facebook as Media E-Retailer (Case Studies of Students in Denpasar City) . Internet Indonesia is growing quite rapidly, of setting developments abroad. According to the Ipsos survey during February 2012, Indonesia was placed as the country with the mostactive  internet  users  in  social  media.  Data shows 90% of the digital consumer in  Indonesia  has  anactive  profile  on  facebook , which Indonesia's second higest state and global level after the United State (Marketing No.12/XI/Desember 2011). The purpose of this study was to investigate the use of exploratory social network / facebook as an e-retailer in the fulffillment of needs among students in the city of Denpasar.  Investigation indicated that about 82 percent are rated internet/ facebook more  than 3 years ago and use it as an e-retailer in the fulfillment of needs, such as  communication needs, the needs of  college,  fashion,  stationery,  food, mobile phones to computers. So the social network /  facebook as an e-retailer has been very effective and efficient in meeting the various needs. Abstrak: Jejaring Sosial/ Facebook Sebagai Media E-Pengecer (Studi Kasus Mahasiswa di Kota Denpasar). Internet di Indonesia berkembang cukup pesat, mengimbangi perkembangan diluar negeri.Menurut survei Ipsos selama Februari 2012, Indonesia ditempatkan sebagai negara dengan pengguna internet paling aktif di media sosial . Data menunjukkan 90% dari konsumen digital di Indonesia memiliki profil aktif di facebook , dimana Indonesia menjadi negara tertinggi dan kedua di tingkat global setelah Amerika Serikat ( Marketing No.12/XI/Desember 2011). Adapun tujuan penelitian ini adalah untuk melakukan investigasi eksplorasi pemanfaatan jejaring sosial /facebook sebagai e-pengecer dalam pemenuhan kebutuhan dikalangan mahasiswa di Kota Denpasar. Investigasi menunjukkan sekitar 82 persen sudah pengenal internet/ facebook lebih dari 3 tahun yang lalu dan memanfaatkannya sebagai e-pengecer dalam pemenuhan kebutuhannya, seperti kebutuhan komunikasi, kebutuhan kuliah, fashion , alat-alat tulis, makanan, handphone hingga komputer. Sehingga jejaring sosial/ facebook sebagai e-pengecer dirasakan sangat efektif dan efisien dalam pemenuhan berbagai kebutuhan.   Kata kunci : jejaring sosial, facebook , e-pengecer, mahasiswa
Keywords: jejaring sosial, facebook, e-pengecer, mahasiswa